1979
DOI: 10.1037/0021-843x.88.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Imagery, encoding, and retrieval of information from memory: Some specific encoding-retrieval changes in Huntington's disease.

Abstract: Mixed lists of 10 high-imagery and 10 low-imagery words were stimuli in a prompted, free-recall experiment. On each trial, only words not recalled on the previous trial were presented again as stimuli. Normal controls recalled more words on each test of recall than did patients with Huntington's disease. Controls remembered more high-imagery words after fewer presentation trials and could recall them with greater consistency than low-imagery words. Patients with Huntington's disease required far more trials to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…This might explain why previous studies have found no effects of duration of illness upon cognitive function with materials that were heterogeneous with respect to stimulus concreteness (Ack et af., 1961 ;Bale, 1973;Fallstriim, 1974;Franceschi et ai., 1984;Ryan et aI., 1984). From a theoretical point of view, similar patterns of results have been obtained in studies of patients with closed head injury (Richardson, 1979;Richardson & Snape, 1984) and with Huntington's disease (Weingartner, Caine & Ebert, 1979). In these investigations, a selective deficit in the recall of concrete material has been ascribed to a specific impairment in the use of mental imagery as a form of elaborative memory code.…”
Section: Discussionsupporting
confidence: 62%
“…This might explain why previous studies have found no effects of duration of illness upon cognitive function with materials that were heterogeneous with respect to stimulus concreteness (Ack et af., 1961 ;Bale, 1973;Fallstriim, 1974;Franceschi et ai., 1984;Ryan et aI., 1984). From a theoretical point of view, similar patterns of results have been obtained in studies of patients with closed head injury (Richardson, 1979;Richardson & Snape, 1984) and with Huntington's disease (Weingartner, Caine & Ebert, 1979). In these investigations, a selective deficit in the recall of concrete material has been ascribed to a specific impairment in the use of mental imagery as a form of elaborative memory code.…”
Section: Discussionsupporting
confidence: 62%
“…Recognition is generally intact, but recall is deficient [17,18]. Executive function has long been characterized as deficient in HD.…”
Section: Cognitive Changesmentioning
confidence: 99%
“…The WMS confirmed the presence of at least a moderate impairment in memory in all of these patients (see Table 1). The laboratory memorylearning procedure used to evaluate patients included a task used by many laboratories to measure changes in episodic memory functions (18,19) as well as other laboratory procedures previously developed in this laboratory to assess disturbances in learning and memory in various patient groups (20,21). The commonly used episodic memory-learning task is one in which subjects are repeatedly presented the same 12 unrelated words until they could all be correctly recalled (a method in which subjects were selectively reminded of those words forgotten on previous recall trials until all words were recalled but for no more than ten learning-test trials).…”
Section: Forms Of Memory Failurementioning
confidence: 99%